Pengembangan Karir Di Era Milenial - Rifa’atul Maftuhah (Universitas Muhammadiyah Surabaya, 2017)
ABSTRACT Career development refers to the process by which employers and academics working in research, teaching, and / or administrative roles manage various tasks, behaviors, and experiences in and across work and organization over time, and career concepts without borders characterize Career patterns that emerge that depend less on the career management of traditional organizations. By using social cognitive career theory and life span, the theory of living space. That careers without borders have an effect on employee career development through electronics in the millennial era, so that the leadership or HRD when going to do a promotion can see the employee's portfolio online Key Words: Development, Development career, millirnisl